Gender differences in depressive symptoms among Chinese older adults based on fairlie decomposition analysis - Lei Yuan; Boyang Yu; Yan Bing; Maolin Du; Zhe Zhao; Jinhai Sun (Heliyon, 2023)
This study aimed to investigate the factors influencing depressive symptoms among Chinese older adults based on gender differences. Data from the eighth wave of Chinese Longitudinal Health Longevity Survey were used. We analyzed the influencing factors of depressive symptoms reported by older adults using the chi-squared test and logistic model. Fairlie decomposition analysis was performed to quantify the contribution level of each influencing factor. We found that 11.71 % of older adults met the CES-D-10 criteria for depressive symptoms. Females (13.89 %) reported a significantly higher level of depressive symptoms than males (9.24 %). Age, residence, sleeping time, exercise, activities of daily living functional disability, instrumental activity of daily living functional disability, and living status influenced depressive symptoms in older adults. Higher education and lower body mass index were only significant in male, whereas middle annual income and exercising were significant only in female. The Fairlie decomposition model explained the reasons for 75.64 % of the gender differences in depressive symptoms, with instrumental activity of daily living functional disability (33.60 %), age (−17.79 %), and education level (17.41 %) being major factors affecting gender differences in depressive symptoms. This is the first nationwide study to examine gender differences in depressive symptoms among older adults. These results provide a basis for relevant Chinese government departments to formulate policies to prevent and control depressive symptoms.